2016
DOI: 10.1080/00140139.2016.1259508
|View full text |Cite
|
Sign up to set email alerts
|

Accident history, risk perception and traffic safe behaviour

Abstract: This study clarifies the associations between accident history, perception of the riskiness of road travel and traffic safety behaviours by taking into account the number and severity of accidents experienced. A sample of 525 road users in Cameroon answered a questionnaire comprising items on perception of risk, safe behaviour and personal accident history. Participants who reported involvement in more than three accidents or involvement in a severe accident perceived road travel as less risky and also reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 35 publications
2
35
0
1
Order By: Relevance
“…According to the decision-making perspective that explains the relationship between perception of risk and the adoption of protective behaviors, if individuals perceive their vulnerability to the risk take protective behaviors [21]. A study in China about individuals' intention to drive after drinking showed that feeling of invulnerability influenced intention by promoting favorable attitudes toward driving after alcohol use [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the decision-making perspective that explains the relationship between perception of risk and the adoption of protective behaviors, if individuals perceive their vulnerability to the risk take protective behaviors [21]. A study in China about individuals' intention to drive after drinking showed that feeling of invulnerability influenced intention by promoting favorable attitudes toward driving after alcohol use [27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous research on pedestrians' behavior has shown that pedestrian previous history of traffic accidents was one of the determinant predictors of pedestrian's decision on how to behave while road crossing [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the increasing number of work-related incidents in the Iranian petrochemical industry, it is important to more fully understand workers' perceptions of the factors affecting safe behaviour and how to promote and maintain it. The attitudes and experiences of workers, supervisors, and safety o cials, in particular, are an important source of evidence for identifying the factors associated with the occurrence of dangerous incidents [25]. Accordingly, the aims of this study are to (a) explore workers', supervisors' and safety managers' perceptions of safety in a petrochemical company in Iran, and (b) identify factors that discourage safe behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous research on pedestrians' behavior has shown that pedestrian previous history of traffic accidents was one of the determinant predictors of pedestrian's decision on how to behave while road crossing [17,18].…”
mentioning
confidence: 99%